2014
DOI: 10.1039/c3gc42355g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of organosolv switchgrass lignin by using high performance liquid chromatography/high resolution tandem mass spectrometry using hydroxide-doped negative-ion mode electrospray ionization

Abstract: Method for identification of compounds in organosolv lignin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 42 publications
9
111
1
1
Order By: Relevance
“…[22-29, 31, 34-36] Given that the compounds studied are representative of the compounds observed in degraded lignin mixtures [36] andc ontain similar functionalities, MS n is extremely important for identification of unknownl ignin degradation products. Hence, it is not surprising that previous studies that only utilized MS 2 or MS 3 experiments were unable to identify all of the functionalities in the analytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22-29, 31, 34-36] Given that the compounds studied are representative of the compounds observed in degraded lignin mixtures [36] andc ontain similar functionalities, MS n is extremely important for identification of unknownl ignin degradation products. Hence, it is not surprising that previous studies that only utilized MS 2 or MS 3 experiments were unable to identify all of the functionalities in the analytes.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Most of these previouss tudies relied on two [23-26, 28, 29, 31, 34, 35, 38] (MS 2 )o rt hree [22,27,36] (MS 3 )s tages of mass spectrometry,t hat is, only the fragment ions of the deprotonated molecules and their fragment ions were examined. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Most of these previouss tudies relied on two [23-26, 28, 29, 31, 34, 35, 38] (MS 2 )o rt hree [22,27,36] (MS 3 )s tages of mass spectrometry,t hat is, only the fragment ions of the deprotonated molecules and their fragment ions were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Other ionization methods, such as positive ion mode ESI or atmospheric pressure chemical ionization (APCI), either cause extensive fragmentation or form multiple ion types for each compound [11]. When used in HPLC/ tandem mass spectrometry experiments, negative ion mode ESI facilitates the analysis of complex lignin degradation product mixtures [12,13]. Structural information for the ionized molecules can be obtained via multiple stages of ion isolation and collisionally activated dissociation (CAD) experiments [14].…”
Section: Introductionmentioning
confidence: 99%
“…Structural information for the ionized molecules can be obtained via multiple stages of ion isolation and collisionally activated dissociation (CAD) experiments [14]. However, isomeric ions can have similar CAD fragmentation patterns, making their differentiation challenging [12]. Therefore, new methods for structural elucidation of isomeric aromatic ions are needed.…”
Section: Introductionmentioning
confidence: 99%
“…[16] As Rahimi et al revealed, when the g-OH group was first selectively oxidized, the formed g-CHO end group would induce the cleavage of the C a ÀC b bond through ar etroaldolr eaction, producing aromatic aldehyde and guaiacol, in which 100 %c onversion of compound (c)w as obtained with benzylic carbonyl compounds in 82-98 %i solatedy ield upon addition of AcNH/ TEMPO/HNO 3 /HCl. 64-99 %c onversion of lignin model compoundsP P-ol and PPone to yield 45-97 %p henol,3 8-84 %a cetophenone, and 6-86 %b enzoic acid under various reactionc onditions such as 0.4-1 MPa O 2 at 80-185 8Cf or 6-48 h( Ta ble S1 in the Supporting Information).…”
Section: Introductionmentioning
confidence: 99%